1995
DOI: 10.1161/01.cir.92.9.322
|View full text |Cite
|
Sign up to set email alerts
|

Comparison by Computerized Numeric Modeling of Energy Losses in Different Fontan Connections

Abstract: The atriopulmonary connection produces higher energy losses than the cavopulmonary connection (+/- 1 mm Hg at rest). The cavopulmonary connection is more efficient when the connection of the caval veins to the pulmonary artery is asymmetrical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 10 publications
0
62
0
Order By: Relevance
“…With comparative analysis of these methods, and keeping in mind anatomic space constraints, some cautious clinical implications can be made. First, our and other studies [13] have shown the advan tages of caval offsetting and, we believe, that within any given anatomic space constraints, offsetting should be incorporated as the first step in all TCPC designs. Whether the SVC should be offset more toward the left PA as in the extracardiac TCPC group or toward the right PA as in our intraatrial TCPC group, has not been determined by this study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…With comparative analysis of these methods, and keeping in mind anatomic space constraints, some cautious clinical implications can be made. First, our and other studies [13] have shown the advan tages of caval offsetting and, we believe, that within any given anatomic space constraints, offsetting should be incorporated as the first step in all TCPC designs. Whether the SVC should be offset more toward the left PA as in the extracardiac TCPC group or toward the right PA as in our intraatrial TCPC group, has not been determined by this study.…”
Section: Discussionmentioning
confidence: 85%
“…Subsequently, an in vivo magnetic resonance imaging study has also demon strated improved flow dynamics in the TCPC over the atriopulmonary connection [9]. In a recent study, compu tational modeling of different types of TCPC demon strated that offsetting of the caval connection was efficient [13]. Paralleling the in vitro studies and learning from the insights therein, many institutions have continued to modify the TCPC design.…”
Section: Flow At Connection Sitementioning
confidence: 99%
“…On the basis of the results of those experiments, they advocated the use of TCPC that was designed to produce a more streamlined flow pattern that should lead to less energy loss. Subsequent in vitro 7,[17][18][19][20][21] and computational 8,18,19 studies confirmed those observations. The effect of progressive right atrial dilatation on energy loss and resistance to flow was recently studied by Lardo and associates 20 in an in vitro flow model of explanted sheep hearts with APA-type Fontan pathways.…”
Section: Discussionmentioning
confidence: 57%
“…Other investigators studied various geometries of TCPC, attempting to find the most efficient connection. 7,8,18,19,21,22 Although these in vitro and computational experiments provided important information regarding isolated aspects of the Fontan circulation, they have not been validated in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation